The role of cdc2 in the expression of herpes simplex virus genes - Advani, Sunil J. (The National Academy of Sciences, 2000)
Earlier reports have shown that cdc2 kinase is activated in cells infected with herpes simplex virus 1 and that the activation is mediated principally by two viral proteins, the infected cell protein 22 (ICP22) and the protein kinase encoded by U(L)13. The same proteins are required for optimal expression of a subset of late (γ(2)) genes exemplified by U(S)11. In this study, we used a dominant-negative cdc2 protein to determine the role of cdc2 in viral gene expression. We report the following. (i) The cdc2 dominant-negative protein had no effect in the synthesis and accumulation of at least two α-regulatory proteins (ICP4 and ICP0), two β-proteins (ribonucleotide reductase major subunit and single-stranded DNA-binding protein), and two γ(1)-proteins (glycoprotein D and viral protease). U(S)11, a γ(2)-protein, accumulated only in cells in which cdc2 dominant-negative protein could not be detected or was made in very small amounts. (ii) The sequence of amino acids predicted to be phosphorylated by cdc2 is present in at least 27 viral proteins inclusive of the regulatory proteins ICP4, ICP0, and ICP22. In in vitro assays, we demonstrated that cdc2 specifically phosphorylated a polypeptide consisting of the second exon of ICP0 but not a polypeptide containing the sequence of the third exon as would be predicted from the sequence analysis. We conclude that cdc2 is required for optimal expression of a subset of γ(2)-proteins whose expression is also regulated by the viral proteins (ICP22 and U(L)13) that mediate the activation of cdc2 kinase.